2017
DOI: 10.1159/000479320
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 27, a Novel Regulator of Transforming Growth Factor β Induced Resistance to Cisplatin in A549 Cell

Abstract: Lung cancer is one of the major causes of cancer morbidity and mortality around the world, and the resistance to cisplatin is a critical issue to chemotherapy in lung cancer patients. Transforming growth factor β (TGF-β) signal pathway abnormality is widely observed in drug resistance during lung cancer chemotherapy. Here, we investigated the effects of heat-shock protein 27 (HSP27) in the TGF-β-induced cisplatin resistance in lung cancer cell. In this study, our results indicated that the mRNA and protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Transforming growth factor β (TGF-β) signal pathway abnormality is widely observed in drug resistance during lung cancer chemotherapy. TGF-β induces the mRNA and protein expression of HSP27 in human lung cancer cell (A549) and the knockdown of HSP27 blocks TGF-β-induced cisplatin resistance via decreasing cell viability and increasing cell apoptosis in A549 cell 23 . It is reported that HSP27 is highly expressed in lung cancer tissues from mice, as well as in a lung cancer cell line.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transforming growth factor β (TGF-β) signal pathway abnormality is widely observed in drug resistance during lung cancer chemotherapy. TGF-β induces the mRNA and protein expression of HSP27 in human lung cancer cell (A549) and the knockdown of HSP27 blocks TGF-β-induced cisplatin resistance via decreasing cell viability and increasing cell apoptosis in A549 cell 23 . It is reported that HSP27 is highly expressed in lung cancer tissues from mice, as well as in a lung cancer cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue microarray (TMA) blocks were prepared using lung cancer tissue and adjacent normal tissue from 76 lung cancer patients according to the method published previously 23 . The TMAs were constructed with a tissue array instrument (Beecher Instruments, Manual Tissue Arrayer, USA) by removal of a tissue core from the donor block using a thin-walled needle with an inner diameter of approximately 2.0 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blockage of TGF-β-mediated cisplatin resistance and decrease of cell viability, and increase of cell apoptosis by knockdown of HSP27 [99] Lung cancer stem cells…”
Section: Hsp27mentioning
confidence: 99%
“…In laryngeal cancer cells, the overexpression of HSP27 exerts cellular resistance against various cytotoxic agents, such as cisplatin and staurosporin, by inducing cell cycle arrest and remodeling actin polymerization involved in drug uptake [97]. In lung cancer, HSP27 promotes TGF-β-induced cisplatin resistance through regulation of SMAD3 [99]. In particular, lung cancer stem cells showed decreased apoptotic response to treatment with superoxide, cisplatin, and gemcitabine when HSP27 was hyperactivated [100].…”
Section: Hsp40mentioning
confidence: 99%